Pektin Dari Daun Cincau Rambat (Cyclea barbata M.) dan Aplikasinya Dalam Bidang Biomedis: Review - Sahamastuti, Agnes Anania Triavika (Publikasi Indonesia, 2025)
Pectin is a natural polysaccharide widely utilized in the food, pharmaceutical, and biomedical industries due to its biodegradable, biocompatible, and non-toxic properties. However, the current commercial sources of pectin remain limited to citrus peels and apple pomace, raising concerns about sustainability and raw material diversification. Therefore, exploration of alternative pectin sources is required. One promising candidate is Cyclea barbata Miers, a traditional Indonesian plant commonly used in refreshing beverages and herbal medicine. This study aims to assess the potential of Cyclea barbata leaves as an alternative pectin source by reviewing extraction yield, degree of esterification, and its possible applications. The method employed includes literature review and analysis of previous empirical data, which indicate that pectin yield ranges between 2.6–13.04% with a degree of esterification varying from 4–94.87%, depending on extraction conditions. These findings confirm that factors such as solvent type, pH, and temperature significantly influence pectin characteristics. The implications of this study highlight the potential of Cyclea barbata-derived pectin for various health-related applications, including pectin–chitosan membranes for wound dressings, emulsifiers, and biopolymer matrices in catalytic nanomaterial synthesis. With further research focusing on extraction optimization, comprehensive molecular characterization, and biological activity testing, Cyclea barbata pectin could be developed into a high-value local biomaterial that supports sustainability and self-reliance in natural-based industries.